Short-term efficacy and safety of a lower dose of polyethylene glycol recombinant human growth hormone in children with growth hormone deficiency: A randomized, dose-comparison study - Zhouhong Jiang; Xuefeng Chen; Guanping Dong; Yin Lou; Jianping Zhang; Xinran Cheng; Jiayan Pan; Wei Liao; Jinzhun Wu; Xiaodong Huang; Xianjiang Jin; Deyun Liu; et al. (Frontiers in Pharmacology, 2022)
Objective: Polyethylene glycol recombinant human growth hormone (PEG-rhGH, Jintrolong®) is the first long-acting rhGH preparation that is approved to treat children with growth hormone deficiency (GHD) in China. Clinical experience with dose selections of PEG-rhGH is scarce. The present study compared the efficacy and safety of a lower dose to increase dosing regimens of PEG-rhGH treatment.Methods: A multicenter, randomized, open-label, dose-comparison clinical study was conducted to compare the improvements in the height standard deviation score (Ht SDS), height velocity (HV), insulin-like growth factor-1 (IGF-1) SDS, and safety profiles of children with GHD who are treated with 0.2 mg/kg/week of PEG-rhGH dose or 0.14 mg/kg/week for 26 weeks.Results: Ht SDS, HV, and IGF-1 SDS increased significantly after PEG-rhGH treatment in the two dose groups (p < 0.05). The improvements of Ht SDS, HV, and IGF-1 SDS were more significant in the high-dose group than in the low-dose group (p < 0.05). Ht SDS improvement in low-dose group was not non-inferiority to that in the high-dose group (p = 0.2987). The incidences of adverse events were comparable between the two groups.Conclusion: The improvements of Ht SDS, HV, and IGF-1 SDS were more significant in the high-dose group than in the low-dose group (p < 0.05). PEG-rhGH at the dose of 0.14 mg/kg/week was effective and safe for children with GHD.Clinical Trial Registration:clinicaltrials.gov, identifier NCT02908958.